Characteristics and outcomes of cancer patients with infection in an intensive care unit (Research, Society and Development, 2022)
Introduction: Cancer remains among the leading causes of death. Due to its characteristics and the high aggressiveness of the treatment, the need for intensive care is common. A significant part of admissions to intensive care units (ICU) can be associated with infections, with sepsis being the main complication. Thus, it is important to know the epidemiological profile for early diagnosis and adequate management, avoiding unfavorable outcomes. Objective: To characterize clinical aspects, cultures performed and outcomes identified in cancer patients admitted to an oncology ICU. Method: A descriptive, retrospective observational study with cancer patients admitted to the ICU of a cancer hospital diagnosed with infection between March 1 and July 31, 2021. Patients with solid or hematological cancer, over 18 years of age, of both sexes, hospitalized in the ICU for more than 24 hours and diagnosed with infection. Results: Of the 124 patients, 75% were diagnosed with infection. 51.6% were female and the mean age was 57 ±16 years. The mean length of stay was 10 ±11 days, with respiratory causes as the main reason (42.9%). The main focus of infection was the respiratory tract (43.9%). 45.9% had sepsis and 18.4% had septic shock. The most common microorganisms were gram-negative bacteria (58.6%). 28 of the microorganisms were multiresistant. Conclusion: A high occurrence of infection and a high mortality rate were identified, which may be related to infections or cancer treatment and/or advanced stage of cancer. A high amount of multidrug-resistant bacteria was identified, highlighting the importance of the rational use of antimicrobials.